Perfluorooctanoic acid exposure alters polyunsaturated fatty acid composition, induces oxidative stress and activates the AKT/AMPK pathway in mouse epididymis. (September 2016) - Lu, Yin; Pan, Yitao; Sheng, Nan; Zhao, Allan Z.; Dai, Jiayin
Abstract: Perfluorooctanoic acid (PFOA) is a degradation-resistant compound with a carbon-fluorine bond. Although PFOA emissions have been reduced since 2000, it remains persistent in the environment. Several studies on laboratory animals indicate that PFOA exposure can impact male fertility. Here, adult male mice received either PFOA (1.25, 5 or 20 mg/kg/d) or an equal volume of water for 28 d consecutively. PFOA accumulated in the epididymis in a dose-dependent manner and resulted in reduced epididymis weight, lower levels of triglycerides (TG), cholesterol (CHO), and free fatty acids (FFA), and activated AKT/AMPK signaling in the epididymis. Altered polyunsaturated fatty acid (PUFA) compositions, such as a higher arachidonic acid:linoleic acid (AA:LA) ratio, concomitant with excessive oxidative stress, as demonstrated by increased malonaldehyde (MDA) and decreased glutathione peroxidase (GSH-Px) in the epididymis, were observed in epididymis tissue following treatment with PFOA. These results indicate that the epididymis is a potential target of PFOA. Oxidative stress and PUFA alteration might help explain the sperm injury and male reproductive dysfunction induced by PFOA exposure. Highlights: PFOA exposure altered polyunsaturated fatty acid composition in epididymides. Triglyceride level and AKT/AMPK signaling strength were detected. PFOA exposure resulted in oxidative stress in the epididymis.